Improved peanut varieties - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The first improved varieties of peanuts developed by ICRI SAT's Regional Program for Southern Africa are now being tested by national institutes to compare them with local varieties. Those that are resistant to rosette disease, a virus that impairs...